New Iterative Method for the Solution of Fractional Damped Burger and Fractional Sharma-Tasso-Olver Equations - Mohammad Jibran Khan; Rashid Nawaz; Samreen Farid; Javed Iqbal (Complexity)
The new iterative method has been used to obtain the approximate solutions of time fractional damped Burger and time fractional Sharma-Tasso-Olver equations. Results obtained by the proposed method for different fractional-order derivatives are compared with those obtained by the fractional reduced differential transform method (FRDTM). The 2nd-order approximate solutions by the new iterative method are in good agreement with the exact solution as compared to the 5th-order solution by the FRDTM.